PTH-009 Endoscopic closure of acute perforations of the gastrointestinal tract in animal models: a systematic review and meta-analysis. (17th June 2017) - Gabr, A; Ammar, N; Houssini, MEl; Summerton, C; Rutter, M
Abstract : Introduction: Acute perforations are one of the recognised complications of both diagnostic and therapeutic gastrointestinal endoscopy. For decades, surgical treatment has been the standard of care, but endoscopic closure has become a more popular approach, due to feasibility and the reduction of the burden of surgery, combined with the availability of various endoscopic closure devices.We aimed to assess the technical and clinical success and safety of endoscopic closure, in total, and for each endoscopic device used in closing acute perforations in animal models. Method: Medical literature (Cochrane library, EMBASE, MEDLINE) from 1966 till September 2016 was searched. A systematic review and meta-analysis were performed on studies reporting technical and clinical success of endoscopic closure of acute perforations, according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines. Results: 46 studies on animal models were identified. 15 studies, including 4 randomised controlled trials, met our inclusion criteria (acute, less than 24 hours, iatrogenic, no fistulas or leaks, clear documentation of the method of closure, and technical and clinical success and 5 cases or more of endoscopic closure per study), were analysed. A total of 214 endoscopic closures were attempted in these studies. The overall technical success rate was 94.8% (n=201/214, 95% CI: 92%>97.6%), clinical success was 92.3% (n=189/214, 95% CI: 88.8%>95.8%), and complication rate was 4.2% (n=6/214, 95% CI: 1.6%>6.8%).Technical success for endoclip closure was 84.9% (95% CI: 71.4%>93.6%), and clinical success was 83.2% (95% CI: 69.5%>92.5%), and complication rate was 2.7% (95% CI: 90.12%>99.88%).For OTSC (Over the scope clip device), technical success was 97% (95% CI: 88%>99.7%), clinical success was 97% (95% CI: 88%>99.7%), and complication rate was 1.87% (95% CI: 91.2%>98.8%).The technical success for endosuturing (endoscopic suturing device) was 92.7% (95% CI: 82% to 98%), clinical success was 87% (95% CI: 74.9%–94.8%), complication rate was 1.9% (95% CI: 91.1%>98.9%). Conclusion: Our study suggests that endoscopic closure is a suitable treatment option for acute iatrogenic gastrointestinal perforations with a reasonable technical and clinical success, and low complication rate. Further confirmation from prospective studies in human is needed. Disclosure of Interest: None Declared